An Update on Scaffold Devices for Rotator Cuff Repair. Issue 3 (September 2017) - Amini, Michael H.; Ricchetti, Eric T.; Iannotti, Joseph P.; Derwin, Kathleen A.
Abstract : The annual volume of rotator cuff repairs in the United States is roughly 250, 000, and failure rates still range from 20% to 70% in most studies despite significant advances in surgical technique and rehabilitation protocols. Even many "healed" repairs continue to have pain, weakness, and dysfunction, a phenomenon that may be explained by "Failure with continuity, " where the healing tendon retracts from the repaired location without a structural defect, leaving interposed scar tissue. To improve clinical outcomes, there is a need to minimize the rate of structural failure and minimize the failure with continuity that occurs after rotator cuff repair. Scaffold devices, in the form of extracellular matrix or synthetic grafts, hold promise in their abilities to mechanically and/or biologically augment repair sites. However, these devices can be technically challenging to apply, and the surgeon must be proficient in their use. To justify the increased operative time and cost associated with their use, we must also demonstrate the ability of these devices to improve structural and clinical outcomes.